SURVEI EFEKTIVITAS LATIHAN PADA EKSTRAKURIKULER SEPAK BOLA DI SMP NEGERI 4 DEDAI - Anggia, Oky (Universitas Tanjungpura, 2019)
The purpose of this study was to determine how much the effectiveness of exercise on the extracurricular soccer in SMP Negeri 4 Dedai. The method used in this research was quantitative descriptive with a from of research whith method of survey. The population in this research was the process of exercise extracurricular soccer in SMP Negeri 4 Dedai the academic year 2018/2019. And sample is the process of exercise on the extracurricular soccer even semester of the academic year 2018/2019. Data collection techniques used incidental sampling method, a tool for collecting data by observing and recording exercise activities from time to time using stationery. From the results of the research conducted, it can be concluded that the results of the effective average value of students in the first meeting were 15.6 (97.9%), the second meeting was 19.5 (97.9%), the third meeting was 13.3 (95.1%) the fourth meeting 19.7 (98.7) fifth meeting 15.6 (97.9%) sixth meeting 11.9 (99.4%) with a total overall score of 15.9 with a percentage of 97.8% and included in the percentage category which is very effective.